Inflation, Asset Prices, and the Term Structure of Interest Rates in Monetary Economies - Bakshi, Gurdip S.; Chen, Zhiwu (Review of Financial Studies, 1996)
[This article offers a tractable monetary asset pricing model. In monetary economies, the price level, inflation, asset prices, and the real and nominal interest rates have to be determined simultaneously and in relation to each other. This link allows us to relate in closed form each of the dependent entities to the underlying real and monetary variables. Among other features of such economies, inflation can be partially nonmonetary and the real and nominal term structures can depend on fundamentally different risk factors. In one extreme, the process followed by the real term structure is independent of that followed by its nominal counterpart.]